2022
DOI: 10.1007/s10834-022-09879-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdowns and Female Employment: Evidence from the Philippines

Abstract: Using labor force survey (LFS) data collected before and during the COVID-19 lockdowns in the Philippines, we showed that hard lockdowns had a larger negative impact on the employment of women who had minor children compared to women who did not have minor children. Among Southeast Asian countries, the Philippines was among the hardest-hit by the pandemic, in terms of both the number of infected and its economic toll. The large economic toll was partly attributable to the extreme and militarized lockdown impos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A situation that occurred to a lesser extent for women who worked in the government sector due to their working and health conditions. Ducanes and Ramos (2023), in the case of the Philippines, found that within the female group, women with children suffered the impacts of the pandemic in the workplace to a greater extent. Effect that Tverdostup (2022) observes will impact gender inequality in the long term in Estonia.…”
Section: State Of the Art: The Consequences Of Covid‐19 On Female Emp...mentioning
confidence: 99%
See 1 more Smart Citation
“…A situation that occurred to a lesser extent for women who worked in the government sector due to their working and health conditions. Ducanes and Ramos (2023), in the case of the Philippines, found that within the female group, women with children suffered the impacts of the pandemic in the workplace to a greater extent. Effect that Tverdostup (2022) observes will impact gender inequality in the long term in Estonia.…”
Section: State Of the Art: The Consequences Of Covid‐19 On Female Emp...mentioning
confidence: 99%
“…Abdel-Rahman et al (2023) determined the factors that negatively affected the female workforce in five Arab countries-Egypt, Morocco, Sudan, Jordan and Tunisia), observing that women with high family responsibilities (childcare and housework) were seriously affected and lost their jobs. A situation that occurred to a lesser extent for women who worked in the government sector due to their working and health conditions Ducanes and Ramos (2023),. in the case of the Philippines, found that within the female group, women with children suffered the impacts of the pandemic in the workplace to a greater extent.…”
mentioning
confidence: 99%
“…The recent economic fluctuations and the COVID-19 pandemic have heightened their need for adaptive and agile strategies (Ducanes and Ramos, 2022). This adaptive nature often leads them to seek flexible work arrangements, yet home offices and other "third places" like cafes or libraries fall short of providing a conducive work environment, often leading to issues like work-family conflicts and cognitive employment insecurity (Antonucci et al, 2021;Molina, 2021).…”
Section: Introductionmentioning
confidence: 99%